APPLIED EU QUALITY SCHEMES AND ORGANIC PRODUCTS ON ROMANIAN MARKET - Dan Marius, Voicilas; Cornelia-Florentina, Alboiu (Economics of Agriculture, 2014)
The aim of the paper is to identify the market potential for products produced and processed according to the EU quality schemes (organic products, PDO, PGI and TSG) on Romanian market. It provides a description of EU and national policies related to development of new markets like organic, PDO, PGI and TSG products, in particular PGI market. The structure of the paper contains an analysis of the organic products and, separately, the analysis of PGI products in Romania, with examples of products under EU quality schemes. During the analysis, we focused on the following aspects: legal frame, institutions and implementation of the quality schemes, supply side, demand side, trade, investments in the field, problems identified and tendencies. It puts in evidence the main characteristics of the country, tendencies, challenges and particularities, which define the groups of products analysed. The example given in text tries to show practical aspects and ways of implementation of the EU quality schemes, for Romania. The paper provides general conclusions resulted from the EU quality schemes implementations in Romania. In the same time, we identify a few difficulties regarding the expansion of the market. By present paper we open new discussions about trends in the field, future developments and models for a good standard of life.